Pollinator dependence but no pollen limitation for eight plants occurring north of the Arctic Circle - Viviane Koch (Ecology and Evolution, 2020)
Abstract Effective interactions between plants and pollinators are essential for the reproduction of plant species. Pollinator exclusion experiments and pollen supplementation experiments quantify the degree to which plants depend on animal pollinators and the degree to which plant reproduction is pollen limited. Pollen supplementation experiments have been conducted across the globe, but are rare in high latitude regions. To fill this knowledge gap, we experimentally investigated the dependence on animal pollinators and magnitude of pollen limitation in eight plant species north of the Arctic Circle in Lapland, Finland. Our findings show that all plant species were pollinator dependent, but not pollen limited. We discuss several mechanisms that might buffer our focal plants from pollen limitation, including plant and pollinator generalization, and attractive plant traits. Our results demonstrate that many plant species north of the Arctic Circle are currently receiving adequate pollinator service and provide a baseline for future comparisons of pollinator dependence and pollen limitation in the Arctic across space and time.